2007
DOI: 10.1001/jama.297.3.286
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Early Myocardial Infarction in South Asians Compared With Individuals in Other Countries

Abstract: and Nepal account for about a quarter of the world's population and contribute the highest proportion of the burden of cardiovascular diseases compared with any other region globally. [1][2][3] South Asian migrants living in several countries have higher death rates from coronary heart disease (CHD) at younger ages compared with the local population despite apparently lower levels of conventional risk factors. [4][5][6][7][8] Deaths related to cardiovascular disease also occur 5 to 10 years earlier in South As… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

40
678
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 825 publications
(723 citation statements)
references
References 48 publications
40
678
1
4
Order By: Relevance
“…The nutritional consequences of migrating from a low-income country to the US are similar to the nutritional consequences of migrating from a rural lifestyle to an urban lifestyle and similar to the effects of ''modernization'' in developing countries [19][20][21]. These consequences include increases reported for various nutrition-related CVD risk factors, including increased intake of saturated fats (i.e., animal foods), refined carbohydrates, sodium and decreased intake of dietary fiber and potassium [5]. In California, South Asian men ages 25-44 years have three times the relative risk of death from CVD in comparison to the age-matched general population [4].…”
Section: Introductionmentioning
confidence: 83%
See 3 more Smart Citations
“…The nutritional consequences of migrating from a low-income country to the US are similar to the nutritional consequences of migrating from a rural lifestyle to an urban lifestyle and similar to the effects of ''modernization'' in developing countries [19][20][21]. These consequences include increases reported for various nutrition-related CVD risk factors, including increased intake of saturated fats (i.e., animal foods), refined carbohydrates, sodium and decreased intake of dietary fiber and potassium [5]. In California, South Asian men ages 25-44 years have three times the relative risk of death from CVD in comparison to the age-matched general population [4].…”
Section: Introductionmentioning
confidence: 83%
“…People in South Asian countries have earlier incidence and greater premature mortality from cardiovascular disease (CVD) than people in Western countries, a disparity that persists for South Asian immigrants in developed countries [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. A case-control comparison of age of first acute myocardial infarction between five South Asian countries and 47 other countries concluded that the observed disparities could be attributed to higher levels of standard risk factors at earlier ages in South Asians compared to citizens of other countries [5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…2 It is now well known that conventional risk factors (smoking, hypertension, diabetes mellitus, obesity, dyslipidemia, unhealthy diet, and reduced physical activity) together account for more than 95% of population-attributable risk for CVD, and novel risk factors have only a small contribution to make. 3 These risk factors, attributed to a set of life-style changes are prevalent both in urban and rural India. 4 Most previous risk-factor studies have focused on young and middle aged adults, and results from these are usually extrapolated to elderly.…”
Section: Introductionmentioning
confidence: 99%